Excited state behaviour of substituted dipyridophenazine Cr(III) complexes in the presence of nucleic acids. - KELLY, JOHN (My University, 2010)
The photophysics and photochemistry of [Cr(phen)2(dppz)]3+ and its 11,12-substituted derivatives [Cr(phen)2(X2dppz)]3+ {X = Me or F} have been studied in the presence of purine nucleotides or DNA using steady state and time-resolved absorption and luminescence spectroscopy . 5?-Adenosine monophosphate (5?-AMP) shows only a weak interaction with the excited states of each complex. By contrast they are efficiently quenched by 5?-guanosine monophosphate (5?-GMP), consistent with photo-induced electron transfer . Laser flash photolysis spectroscopy in the presence of 5?-GMP suggests that both forward and back electron-transfers are rapid. All complexes also display a strong affinity for DNA and evidence for both static and dynamic quenching mechanisms is provided.
PUBLISHED
Keywords: Biochemistry; Nanoscience & Materials